The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.4049/jimmunol.176.9.5314
|View full text |Cite
|
Sign up to set email alerts
|

RhoG Regulates the Neutrophil NADPH Oxidase

Abstract: RhoG is a Rho family small GTPase implicated in cytoskeletal regulation, acting either upstream of or in parallel to Rac1. The precise function(s) of RhoG in vivo has not yet been defined. We have identified a novel role for RhoG in signaling the neutrophil respiratory burst stimulated by G protein-coupled receptor agonists. Bone marrow-derived neutrophils from RhoG knockout (RhoG−/−) mice exhibited a marked impairment of oxidant generation in response to C5a or fMLP, but normal responses to PMA or opsonized z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 36 publications
3
34
1
Order By: Relevance
“…The striking defect we observed in DOCK2 recruitment to the leading edge of polarised neutrophils upon loss of RhoG indicates that this mechanism is also responsible for linking RhoG and Rac downstream of GPCRs in neutrophils. It is also consistent with previous data indicating P-Rex 2/2 (Dong et al, 2005;Welch et al, 2005), RhoG 2/2 (Condliffe et al, 2006) and DOCK2 2/2 (Kunisaki et al, 2006) neutrophils all display defects in GPCRinduced Rac activity and ROS production. This new pathway for GPCR-mediated control of Rac thus unifies a number of confusing observations in the field of Rho family signalling, by indicating a hierarchical, rather than simply cooperative organisation of GEF input into Rac activation (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The striking defect we observed in DOCK2 recruitment to the leading edge of polarised neutrophils upon loss of RhoG indicates that this mechanism is also responsible for linking RhoG and Rac downstream of GPCRs in neutrophils. It is also consistent with previous data indicating P-Rex 2/2 (Dong et al, 2005;Welch et al, 2005), RhoG 2/2 (Condliffe et al, 2006) and DOCK2 2/2 (Kunisaki et al, 2006) neutrophils all display defects in GPCRinduced Rac activity and ROS production. This new pathway for GPCR-mediated control of Rac thus unifies a number of confusing observations in the field of Rho family signalling, by indicating a hierarchical, rather than simply cooperative organisation of GEF input into Rac activation (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…A key question, therefore, is the extent to which activation of RhoG is the most important function of P-Rex1 and, additionally, the relationship of this function to the activation of its alternative potential substrates Rac1 and Rac2. Separate studies have previously reported that RhoG and P-Rex1 regulate some Rac2-dependent neutrophil functions, such as activation of the NADPH oxidase (Condliffe et al, 2006;Dong et al, 2005;Welch et al, 2005). However, the relatively small effects of P-Rex1 deletion observed in these studies contrast with the more severe defects reported upon RhoG deletion, and thus conflict with our observation that P-Rex1 is the major regulator of RhoG in this system.…”
Section: P-rex1 and Rhog Regulate Fmlp-driven Rac Activity And Nadph contrasting
confidence: 56%
See 2 more Smart Citations
“…It has been established that binding of active RhoG to a complex of Elmo and Dock180 stimulates the GEF activity of Dock180, leading to GTP-loading of Rac1 (deBakker et al, 2004;Katoh and Negishi, 2003;Lu and Ravichandran, 2006). Interestingly, RhoG has been implicated in various cell functions known to be subdued by Yersinia, such as integrin-mediated phagocytosis, transendothelial migration and activation of NADPH oxidase (Condliffe et al, 2006;Nakaya et al, 2006;van Buul et al, 2007).…”
Section: Introductionmentioning
confidence: 99%